2015
DOI: 10.1002/path.4503
|View full text |Cite
|
Sign up to set email alerts
|

The genomic landscape of phaeochromocytoma

Abstract: Phaeochromocytomas (PCCs) and paragangliomas (PGLs) are rare neural crest-derived tumours originating from adrenal chromaffin cells or extra-adrenal sympathetic and parasympathetic tissues. More than a third of PCC/PGL cases are associated with heritable syndromes involving 13 or more known genes. These genes have been broadly partitioned into two groups based on pseudo-hypoxic and receptor tyrosine kinase (RTK) signalling pathways. Many of these genes can also become somatically mutated, although up to one th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
91
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(103 citation statements)
references
References 83 publications
12
91
0
Order By: Relevance
“…Instead the ubiquitous status of driver mutations emphasizes their potential to serve as prognostic and predictive markers as well as identifiers of druggable targets in PPGL. The ultimate implications of genetic heterogeneity in PPGL need to be clarified in future studies using genome-wide single-nucleotide resolution (44). (Continued. )…”
Section: Discussionmentioning
confidence: 99%
“…Instead the ubiquitous status of driver mutations emphasizes their potential to serve as prognostic and predictive markers as well as identifiers of druggable targets in PPGL. The ultimate implications of genetic heterogeneity in PPGL need to be clarified in future studies using genome-wide single-nucleotide resolution (44). (Continued. )…”
Section: Discussionmentioning
confidence: 99%
“…Somatic mutations in TSC2 occur frequently in pancreatic NETs (80). Overview of mutational burden in NETs merged from raw data in (80,85,86,87,98,99,100,104,117,120,121,122,128,136,137). Each dot represents a unique tumor, and the line shows the median number of mutations of each category.…”
Section: Tuberous Sclerosis Complexmentioning
confidence: 99%
“…Whether this gene acts as a disease driver or modifier remains to be identified (120). The genomic landscape of PCC and PGL is associated with relatively low degree of genomic instability having an average of 19 nonsynonymous mutations per tumor (117,121,122). Clinical criteria have classified these tumors accordingly to location into PCCs (adrenal medulla) and PGLs (extra adrenal).…”
Section: Pcc and Pglsmentioning
confidence: 99%
“…Two additional new studies reported whole-exome sequencing of 40 and 31 additional pheochromocytomas and paragangliomas, respectively 250,251 . These studies confirmed the involvement of ATRX, but also reported other potential novel driver alterations including recurrent mutations in FMR1, TP53, MET and CDKN2A, though neither of the studies identified the FGFR1 gene.…”
Section: Discussionmentioning
confidence: 99%